Digital palatal anthropometry in children with and without congenital zika syndrome-associated microcephaly - Bisaia, Aliny; Ambrosio, Eloá Cristina Passucci; Moreira, Kelly Maria Silva; Benedito, Eduarda Cristina de Oliveira; Oliveira, Thais Marchini; Machado, Maria Aparecida Andrade Moreira (Brazilian Dental Science, 2026)
Objective: To digitally compare palatal linear and angular anthropometry in children with and without congenital zika syndromeassociated microcephaly. Material and Methods: Thirty-eight digitized dental molds were divided into two groups: congenital zika syndrome-associated microcephaly (CZS) group and control group (no associated craniofacial anomaly). Linear and angular measurements were performed, as follow: left (I-C’) and right (I-C) anterior intersegment distance, left (I-T’) and right (I-T) anterior-posterior intersegment length, intercanine distance (C-C’), intertuberosity distance (T-T’); left (T’C’I) and right (ICT) deciduous canine angle, and interincisive angle (C’IC). Intraclass Correlation Coefficient, Mann-Whitney test, independent T test, and Pearson Correlation were used for statistical analysis with α=5%. Results: In CZS group, the intertuberosity measurement (T-T’) of boys were statistically higher than that of girls (p=0.0496). The CZS group showed strong correlations for I-C vs. C-C (r=0.919), while the control group showed strong correlations for I-C vs. C-C (r=0.846), I-C vs. C-C (r=0.847), and T-T vs. I-T (r=0.722). The means of angles T’C’I and ICT were greater in CZS group (p=0.0016 and p=0.0313, respectively), while measurement C’IC was greater in control group (p=0.0008). Whereas the linear measurements did not show a statistically significant difference (p>0.05). Conclusion: Children with congenital Zika syndrome–associated microcephaly showed a tendency toward anterior palatal narrowing compared with children without craniofacial anomalies, suggesting the need for early palatal expansion. KEYWORDS Anthropometry; Dental arch; Imaging, three-dimensional; Microcephaly; Zika virus.